2020
DOI: 10.3390/molecules25133104
|View full text |Cite
|
Sign up to set email alerts
|

Juglone Suppresses LPS-induced Inflammatory Responses and NLRP3 Activation in Macrophages

Abstract: The NLRP3 (NACHT, LRR and PYD domains-containing protein 3) inflammasome has been implicated in a variety of diseases, including atherosclerosis, neurodegenerative diseases, and infectious diseases. Thus, inhibitors of NLRP3 inflammasome have emerged as promising approaches to treat inflammation-related diseases. The aim of this study was to explore the effects of juglone (5-hydroxyl-1,4-naphthoquinone) on NLRP3 inflammasome activation. The inhibitory effects of juglone on nitric oxide (NO) production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 35 publications
0
4
0
1
Order By: Relevance
“…It is worth mentioning that a recent research found that colchicine, which is a drug widely used in the treatment of nonspecific inflammation, could combine with cholesterol crystal (CC), an important pathological marker for the vulnerability of atherosclerotic plaques [73]. This combination can reduce the intake of cholesterol crystals by endothelial cells, thus attenuating the cellular oxidative stress and endothelial cell prolapse by regulating the AMPK/SIRT1 signaling pathway [74].…”
Section: Atherosclerosismentioning
confidence: 99%
“…It is worth mentioning that a recent research found that colchicine, which is a drug widely used in the treatment of nonspecific inflammation, could combine with cholesterol crystal (CC), an important pathological marker for the vulnerability of atherosclerotic plaques [73]. This combination can reduce the intake of cholesterol crystals by endothelial cells, thus attenuating the cellular oxidative stress and endothelial cell prolapse by regulating the AMPK/SIRT1 signaling pathway [74].…”
Section: Atherosclerosismentioning
confidence: 99%
“…In addition, juglone exhibits antifungal (e.g., Aspergillus and Penicillium ), antibacterial (e.g., Escherichia coli , Staphylococcus aureus , Bacillus subtilis , and Helicobacter pylori ), antiviral, and antiparasitic activities [ 4 , 7 , 8 ]. However, juglone also suppressed lipopolysaccharides-induced inflammatory responses and NLRP3 inflammasome activation in tumor-derived J774.1 cells [ 9 ]. For these reasons, it has long been used in traditional medicine against various health conditions, including gastrointestinal disorders, cancers, allergies, and different microbial infections [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…İmmün hücreler için, NLRP3 aktivatörlerinin mevcudiyeti tek başına inflamazom oluşumunu ve aktivasyonunu uyarmak için yetersizdir, bunun için bir hazırlama (priming) sinyali (sinyal 1) gereklidir 3 . Makrofaj ya da glia hücrelerinde bulunan PRR'ler tarafından (TLR ya da NLR'ler), PAMP'ların ve DAMP'ların tanınması sonucu enflamasyonu indükleyen NF-κB sinyalizasyonun aktivasyonu ve enflamatuvar sitokinlerin salınması gerçekleşir 12 . İlk sinyal sonucu, IL-6, TNF-α gibi proenflamatuvar sitokinlerin gen transkripsiyonları artar ve doğrudan salınımları gerçekleşir.…”
Section: Nlrp3 Inflamazom İlk (Primer) Sinyalizasyon (Sinyal 1)unclassified